2011
DOI: 10.1182/blood-2010-10-311761
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase RAD18 regulates ubiquitylation and chromatin loading of FANCD2 and FANCI

Abstract: Fanconi anemia (FA) is a rare genetic disorder characterized by bone marrow failure, congenital abnormalities, and an increased risk for cancer and leukemia. Components of the FA-BRCA pathway are thought to function in the repair of DNA interstrand cross-links. Central to this pathway is the monoubiquitylation and chromatin localization of 2 FA proteins, FA complementation group D2 (FANCD2) and FANCI. In the present study, we show that RAD18 binds FANCD2 and is required for efficient monoubiquitylation and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 35 publications
2
68
1
Order By: Relevance
“…This interaction likely facilitates not only a Cdc7-ASK-mediated phosphorylation of RAD18 to prime the latter for interaction with Pol h but also the recruitment of the RAD18-Pol h complex to stalled replication forks. In addition, our finding that the N-terminal region of RAD18 containing the RING domain interacts with ASK is quite intriguing given that FANCD2 and Rad51C also interact with the RING domain of RAD18 (Huang et al 2009;Williams et al 2011). It is possible that a binding partner of RAD18 may determine the optimal DNA damage response pathway upon distinct genotoxic insults.…”
Section: Cdc7-ask Kinase Regulates the Dna Damage Bypass Pathwaymentioning
confidence: 93%
“…This interaction likely facilitates not only a Cdc7-ASK-mediated phosphorylation of RAD18 to prime the latter for interaction with Pol h but also the recruitment of the RAD18-Pol h complex to stalled replication forks. In addition, our finding that the N-terminal region of RAD18 containing the RING domain interacts with ASK is quite intriguing given that FANCD2 and Rad51C also interact with the RING domain of RAD18 (Huang et al 2009;Williams et al 2011). It is possible that a binding partner of RAD18 may determine the optimal DNA damage response pathway upon distinct genotoxic insults.…”
Section: Cdc7-ask Kinase Regulates the Dna Damage Bypass Pathwaymentioning
confidence: 93%
“…After washing extensively with PBST to remove unbound secondary antibody, the slides were for FANC status by immunoblotting as described in recent publications. 45,64,65 All cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, streptomycin sulfate (100 μg/ml) and penicillin (100 U/ml), 5 mM L-glutamine, and cultures were incubated at 37°C in humidified chambers with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we reported that FANCD2 and Rad18 may be co-immunoprecipitated as a complex. 45 Whether Rad18 and FANCD2 associate directly or via other proteins is not known and is beyond the focus of this study. However, it is very common for DNA repair proteins to stabilize their binding partners, and this provides a plausible explanation for the effect of FANCD2-depletion on Rad18 levels.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…[122][123][124][125][126] RAD18-RAD6 catalyzes the monoubiquitination of PCNA on K164, a molecular event necessary for DNA polymerase switching during translesion DNA synthesis (TLS).…”
Section: Fancd2 and Fanci Functionmentioning
confidence: 99%
“…122,126 Genetic disruption of RAD18 or RAD18 depletion via siRNA leads to decreased ICL-induced FANCD2/I monoubiquitination and chromatin binding. [122][123][124][125][126] Furthermore, RAD18-RAD6 mediated monoubiquitination of PCNA on K164 is necessary for efficient FANCD2 monoubiquitination. 122 FANCL was also shown to bind to PCNA directly and PCNA K164 monoubiquitination was shown to be required for FANCL chromatin loading.…”
mentioning
confidence: 99%